Ребенок от 3 до 7 лет: интенсивное воспитание / Лариса Суркова - Суркова Лариса Михайловна (АСТ, 2015)
Экземпляры: ф.8 (20151008) / Инвентарный номер: 56600 / Цена: / Сис.шифр: 88.8 / Авт.знак: С 90 / ГРНТИ: 15.81.65 / ББК: 88.8^VLBC/RL